Pembangunan Hukum Nasional dalam Perspektif Teori dan Filsafat Hukum - Subianta Mandala (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2024)
This paper discusses some strategic issues about national legal development, which is viewed in the light of legal theory and philosophy. The need to replace the laws of the colonial regime has been discussed for quite some time, and in fact, since Indonesia declared its independence. However, the process of replacing the Dutch laws and developing its own national law is quite slow. There are some strategies issues discussed in this writing, namely, among others: what is the legal politics/policy of the issue of legal unification and legal pluralism in Indonesia, what is the legal approach about the development of unwritten and written laws, what is the legal policy to address the issue of adat law as one of the material legal sources for the future Indonesian laws, and how jurisprudence (court decisions) may be used to develop Indonesian national legal system. With those backgrounds, the formulation of the problems is as follows: how can legal theory and philosophy be used as theoretical and philosophical argumentation to address some strategic issues of Indonesian legal development as mentioned above, and what is the legal politics/policy for the development of national legal system of Indonesia, in particular, of those strategic legal issues. The method used in this research paper is normative juridical or library research with a descriptive-qualitative analytical approach. The result of the research shows that, as of today, there are no official documents or any existing laws that comprehensively give direction to the legal politics/policy on the strategic issues of Indonesian legal development. In general, the discussion on the issues of national legal development is limited among legal experts and academicians, and the debate on contentious issues has fundamental arguments based on legal theory/philosophy. So far, legal positivism has a a significant influence on the way we respond to those strategic issues. However, there has been an interesting development recently. We can gradually see a paradigm shifting from legal positivistic to a more sociological, human and ethical approach.